An Exploratory Investigation of Communication Technologies to Alleviate Communicative Difficulties and Depression in Older Adults. (June 2016) - Ruppel, Erin K.; Blight, Michael G.; Cherney, Maura R.; Fylling, Samantha Q.
Objective: To explore associations between older adults' communicative difficulties, depressive symptoms, and e-mail and telephone use with adult children.Method : We examined these associations using data from 1, 634 participants (age M = 71.16, SD = 0.89; 54% female) in the 2011 wave of the Wisconsin Longitudinal Study.Results : Better vision and worse speech were associated with more frequent e-mail contact with the selected child. Worse hearing was associated with more depressive symptoms for participants with low e-mail use but not for those with average or high e-mail use. Telephone use was not associated with communicative difficulties or depressive symptoms.Discussion : This study provides preliminary evidence that older adults might use communication technologies such as e-mail in their close relationships to compensate for communicative difficulties. The text-based format of e-mail might also help older adults mitigate hearing impairments and associated depressive symptoms.